Priority areas of investment in the Republic of Uzbekistan to achieve demographic dividend - Enikeeva, A (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The increase in the share of the working population in the next few years with a moderate number of dependents will create favorabledemographic conditions for economic growth in Uzbekistan - the so-called demographic dividend, which could have a significant positive impact on increasing real incomes, helping to reduce poverty and increase stability. The probability of obtaining a demographic dividend is not guaranteed. To effectively implement it, it is necessary to stimulate economic growth and social development of the Republic of Uzbekistan, provided that adequate investments are made in human capital, the development of a flexible economic model, the introduction of innovative technologies and the expansion of opportunities for young people and women to participate in the socio-economic development of the country